Current Insights Into Adrenal Insufficiency in the Newborn and Young Infant - Buonocore, Federica; McGlacken-Byrne, Sinead M.; del Valle, Ignacio; Achermann, John C. (Frontiers in Pediatrics, 2020)
Adrenal insufficiency is a potentially life-threatening condition that can be difficult to diagnose, especially if it is not considered as a potential cause of a child’s clinical presentation or unexpected deterioration. Children who present with adrenal insufficiency in early life can have signs of glucocorticoid deficiency (hyperpigmentation, hypoglycemia, prolonged jaundice, poor weight gain), mineralocorticoid deficiency (hypotension, salt loss, collapse), adrenal androgen excess (atypical genitalia), or associated features linked to a specific underlying condition. Here, we provide an overview of causes of childhood adrenal insufficiency, with a focus on genetic conditions that present in the first few months of life. Reaching a specific diagnosis can have lifelong implications for focusing management in an individual, and for counseling the family about inheritance and the risk of recurrence.